Removal of aqueous nC60 fullerene from water by low pressure membrane filtration. (15th March 2016) - Floris, R.; Nijmeijer, K.; Cornelissen, E.R.
Abstract: The potential environmental and health risks of engineered nanoparticles such as buckminsterfullerene C60 in water require their removal during the production of drinking water. We present a study focusing on (i) the removal mechanism and (ii) the elucidation of the role of the membrane pore size during removal of nC60 fullerene nanoparticle suspensions in dead-end microfiltration and ultrafiltration mimicking separation in real industrial water treatment plants. Membranes were selected with pore sizes ranging from 18 nm to 500 nm to determine the significance of the nC60 to membrane pore size ratio and the adsorption affinity between nC60 and membrane material during filtration. Experiments were carried out with a dead-end bench-scale system operated at constant flux conditions including a hydraulic backwash cleaning procedure. nC60 nanoparticles can be efficiently removed by low pressure membrane technology with smaller and, unexpectedly, also by mostly similar or larger pores than the particle size, although the nC60 filtration behaviour appeared to be different. The nC60 size to membrane pore size ratio and the ratio of the cake-layer deposition resistance to the clean membrane resistance, both play an important role on the nC60 filtration behaviour and on the efficiency of the backwash procedure recovering the initial membrane filtration conditions. These results become specifically significant in the context of drinking water production, for which they provide relevant information for an accurate selection between membrane processes and operational parameters for the removal of nC60 in the drinking water treatment. Graphical abstract: Highlights: Membrane processes are a viable barrier in minimizing human exposure to fullerene. Effect of pore size was significant in removal and removal mechanism of nC60 . Membranes with pore sizes similar/larger than nC60 pore size show >99% removal. Backwash can remove accumulated cake-layer when cake resistance is higher than membrane resistance.